2019
DOI: 10.1186/s12882-019-1502-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in end-stage renal disease in a high-risk population: the Southern Community Cohort Study

Abstract: Introduction The Southern Community Cohort Study is a prospective study of low socioeconomic status (SES) blacks and whites from the southeastern US, where the burden of end-stage renal disease (ESRD) and its risk factors are high. We tested whether the 2.4-fold elevated risk of ESRD we previously observed in blacks compared to whites was explained by differences in baseline kidney function. Methods We conducted a case-cohort study of incident ESRD cases ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Consistent with the overall population, we found that SO improved sP levels while reducing pill burden in prespecified analyses of Black/African American and Hispanic/Latino patients, populations at increased risk of endstage kidney disease (ESKD) compared with white patients. 19,20 In addition to being disproportionately represented in the ESKD population, 21 Black/African American patients have a higher burden of ESKD-related complications, including secondary hyperparathyroidism and cardiovascular mortality due to elevated sP. [21][22][23][24] Our findings in this subgroup of patients are consistent with those of a post hoc analysis of a Phase 3, open-label trial demonstrating that SO achieved sP control in Black/African American patients with comparable efficacy as sevelamer but offered a lower pill burden.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the overall population, we found that SO improved sP levels while reducing pill burden in prespecified analyses of Black/African American and Hispanic/Latino patients, populations at increased risk of endstage kidney disease (ESKD) compared with white patients. 19,20 In addition to being disproportionately represented in the ESKD population, 21 Black/African American patients have a higher burden of ESKD-related complications, including secondary hyperparathyroidism and cardiovascular mortality due to elevated sP. [21][22][23][24] Our findings in this subgroup of patients are consistent with those of a post hoc analysis of a Phase 3, open-label trial demonstrating that SO achieved sP control in Black/African American patients with comparable efficacy as sevelamer but offered a lower pill burden.…”
Section: Discussionsupporting
confidence: 81%
“…The creatine assays were calibrated, and daily quality checks performed at three levels before sample testing. This sample constitutes 13% of SCCS participants who donated blood, and is comparable with respect to baseline sociodemographic characteristics including racial distribution, low income and high prevalence of CKD risk factors 17. The weighted subcohort included 70.8% black participants and 29.2% white participants, and the SCCS population included 67.3% black participants and 28.6% white participants.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation for the elevated risk of hemorrhage in Black and older individuals may be the increased usage of anticoagulant and antiplatelet medications in these populations which have been shown to predispose to diverticular bleeding [19][20][21] . Especially in Philadelphia where profound racial healthcare inequality exists, Black individuals are more likely to be on long-term anticoagulation or aspirin due to the increased disease burden including hypertension, DVTs/PEs, and diabetes disproportionately affecting this segment of the population [22][23][24][25] . Similarly, patients > 65 years old are more likely to be using antithrombotic medication as older age is a risk factor for almost all vascular disease manifestations [26,27] .…”
Section: Discussionmentioning
confidence: 99%